The new encyclopedia of icebreakers - McLaughlin, Miriam (Pfeiffer, 2004)
The New Encyclopedia of Icebreakers -- the sequel to the best-selling? Encyclopedia of Icebreakers -- gives you 150 innovative activities to energize your training sessions. The book is filled with a variety of activities that will move participants through the stages of group development: forming, storming, norming, performing, and adjourning. Use this new collection to help people get acquainted, build teams, address team or group issues, develop effective working relationships, and improve learning and retention of new information. The final chapter presents specific adjourning activities to help you bring closure to your training or group work, increase skills and knowledge transfer, and transition the participants back to the workplace.